Myxoma of the mitral valve. Issue 2 (August 1979) - Sandrasagra, F A; Oliver, W A; English, T A
Abstract : A case of myxoma of the mitral valve is reported. The clinical features were indistinguishable from left atrial myxoma with prolapse through the mitral valve. Because of the known tendency for these tumours to recur it was treated by wide excision which necessitated replacement of the mitral valve.